(untitled) (Khairulummah, 2025)
The demands of Da‘wah (invitation to Allah) require that a caller (da‘i) be one who delivers glad tidings, facilitates ease, and exhibits patience in the face of people’s stubbornness and harshness. The Prophet ﷺ consistently instructed the Companions to promote glad tidings and ease, highlighting the virtue of Muslims who mingle with others and endure their adversities with patience. Sincerity, freedom from ostentation, and complete avoidance of hypocrisy are fundamental prerequisites in this path, as acts performed for show and the discrepancy between words and deeds can render even the greatest of virtues futile on the Day of Judgment. A da‘i must strive to prevent all forms of polytheism, forbid manifestations such as crosses, uphold the oneness of Allah (Tawḥīd), and be prepared to offer their life in defense of faith, as exemplified in the incident of the seventy reciters. Another essential requirement of da‘wah is that a caller should not prevent anyone from worship, but rather guide them toward righteousness, enjoin good, forbid evil, and patiently endure the trials that accompany this process. The Prophet ﷺ extended his invitation even to close relatives, continuously reminding Abu Talib of the Kalima until his death. Likewise, he taught young companions, such as Ibn ‘Abbas (RA), the principles of divine protection, reliance (tawakkul), and predestination. Thus, the path of da‘wah spans from the beginning to the end of life, encompassing sincerity, monotheism, patience, consistency between word and deed, selflessness, exemplary character, and the continuous effort to connect creation with their Creator.